THE DIFFUSION OF INNOVATION, PERCEPTION OF RISK, USER's TRUST OF ONLINE BANKING TO THE SUCCESS OF COMMERCIAL BANK IN THAILAND - Bupphakham, Tevin (Journal of Buddhist Anthropology, 2022)
The Objectives of this research article were to: 1) study the composition of innovation diffusion factors, reception risk, and user’s trust of online banking, 2) study relation of innovation diffusion, reception risk that affected to user’s trust of online banking, 3) study influence of user’s trust about online banking innovation that affected to the success of commercial banks in Thailand, and 4) to study the success of commercial banks in Thailand, The research was mix method such as quantitative research uses questionnaire as a research tool, sample group that including with 384 people who use online banking services of commercial banks of Thailand, purposive sampling. Data was analyzed using frequency statistics, percentage, mean, standard deviation. And qualitative research uses an in-depth interview form as a research tool. Key informant was: 1) branch manager and 2) branch executive for all 5 persons, purposive sampling. Data was analyzed using content analysis and overview summarizing. The research was found that: 1.composition of factors: 1.1) innovation diffusion ( = 4.42, S.D. = 0.42), 1.2) perceived risk ( = 3.99, S.D. = 0.68), and 1.3) trust ( = 4.12, S.D. = 0.59), 2. The relation was of innovation diffusion found positively correlated with trust, at the middle level, correlation coefficient (r = 0.418) and perceived risk positively correlated with trust at low level so correlation coefficient was (r = 0.514). 3. The influence of trust was warranty, the integrity of the information affects the success of commercial banks. and 4. The success of commercial banks was consists of financial, customer, internal management, and learning and growing.